Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Rôle des valeurs en science: contributions de la philosophie féministe des sciences - Ruphy, Stéphanie (Écologie & politique, 2015)
Cinq décennies d’études féministes sur les sciences ont renouvelé et enrichi significativement les réflexions épistémologiques sur des notions fondamentales comme celles d’objectivité ou de preuve empirique, et plus largement sur la question du rôle des valeurs en science. Nous présentons quelques-unes des positions féministes actuelles les plus influentes au sein de la philosophie des sciences contemporaine, positions qui offrent des alternatives à l’idéal de neutralité de la science et ouvrent la possibilité d’une pratique proprement féministe des sciences. Nous discuterons également du tournant politique de la philosophie des sciences, invitée à se saisir de la question du rôle et des objectifs assignables à la science dans nos démocraties contemporaines.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; cours; discipline; discours dominant; europe; france; phi4336; philosophie; point de vue situé; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie